Barong Landung: Inspirasi Daya Tarik Wisata dan Industri Kreatif di Bali - Anak Agung Gde Raka; Novi Anoegrajekti; Putu Ngurah Suyatna Yasa (Universitas Udayana, 2020)
Barong Landung is a rare and unique Balinese art performance that has the opportunity to be developed as a tourist attraction and a source of inspiration for creative industries. The uniqueness of Barong Landung can be seen from the characters that are associated with the mythology of the King of Bali with his Chinese princesses. This article analyzes the potential of the Barong Landung art performance to be developed as tourist attraction in supporting Bali cultural tourism and a source of creative industries. Data collection is done by observation, interview, and desk research and were analyzed qualitatively using the theory of commodification. The study shows that there were two types of Barong Landung performances namely sacred and profane. The former is for religious ritual, while the latter can be performed for touristic purpose and for source of inspiration of souvenir products that both support Bali cultural tourism.